Forms of the Ancient History: Brazilian contributions to discussions about the Roman Empire - Souza, Dominique Monge Rodrigues de (Romanitas - Revista de Estudos Grecolatinos, 2014)
Review of: JOLY, F. D.; FAVERSANI, F. (Org.). As formas do Império Romano. Mariana: Ed. Ufop, 2014. 107 p.